Multiple plasma metals, genetic risk and serum complement C3, C4: A gene-metal interaction study. (March 2022) - Jiang, Jing; He, Shiqi; Liu, Kang; Yu, Kuai; Long, Pinpin; Xiao, Yang; Liu, Yiyi; Yu, Yanqiu; Wang, Hao; Zhou, Lue; Zhang, Xiaomin; He, Meian; et al.
Abstract: Exposure to metals and metalloids is widely related with human health, and could affect the function of immune system. The complement system links innate and adaptive immunity, and is critically involved in the pathogenesis of inflammatory and immune diseases. The third and fourth components of complement (C3, C4) play key roles in the complement system. However, few studies have examined the relations between multiple metals and complement levels. In this study, based on a total of 2977 participants from the Dongfeng-Tongji cohort, China, we investigated 17 plasma metals and serum C3, C4 levels, and calculated C3/C4-associated genetic risk scores (GRSs) using established single nucleotide polymorphisms. We further explored the potential gene-metal interactions on C3 and C4. After multivariable adjustment, an increment of 10-standard deviation increase in natural log-transformed exposure concentrations of plasma copper was associated with 0.549 (0.489, 0.608) (FDR <0.0001), and 1.146 (0.999, 1.294) (FDR <0.0001) higher natural log-transformed serum C3 and C4 levels, respectively. While each increment of 10-standard deviation of natural log-transformed zinc was associated with a difference of 0.083 (0.024, 0.143) (FDR = 0.049) and 0.007 (−0.138, 0.152) (FDR = 0.935) in log-transformed C3 and C4 levels, respectively. Participants with higher GRS had higher C3 and C4 levels. Furthermore, we found a significant interaction between arsenic exposure and C3-GRS in relation to C3 level ( P interaction = 0.0096). Our results suggested that plasma arsenic would modify the association between C3 genetic predisposition and serum C3 level. We provide new insight into metals exposure on the human immune system. These findings require replication in future research. Graphical abstract: Image 1 Highlights: We found positive linear relations of plasma Cu level with serum C3, C4 levels. There was a positive non-linear relation of plasma Zn level with serum C3 level. We observed an interaction between C3-GRS and plasma As in relation to C3 level.